Mobilizing Religious Resources to Strengthen Social Solidarity: A Case Study of Bumi Ratu Village, Tulang Bawang Regency - Sari, Anggi Novita; Kuswana, Dadang; Muliadi, Muliadi (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study examines how religious resources are mobilized to strengthen social solidarity in Bumi Ratu Village, South Rawajitu District, Tulang Bawang Regency, Lampung, Indonesia. In the context of rural communities that still consider religion as a moral foundation and social guideline, religious values play a central role in regulating community interaction patterns. The theoretical approach used is Resource Mobilization Theory (RMT), which views collective action not as a spontaneous response, but as the result of conscious and organized management of moral, material, human, and symbolic resources. The study was conducted through a qualitative approach with data collection techniques in the form of in-depth interviews, participant observation, and documentation. Three informants were selected purposively: a village head, a religious figure, and a representative of the general public. The results show that religious values, religious figures, mosques, and social networks are the main resources mobilized to build social solidarity. Religious figures act as moral motivators who interpret solidarity as part of the practice of religious teachings, while village leadership utilizes religious legitimacy to mobilize residents in collective activities. The mobilization process takes place through the mechanisms of da'wah, deliberation, organizing mosque-based activities, and reinterpreting social activities as worship. This research confirms that religion is not merely a source of spiritual doctrine, but rather a strategic instrument in building social solidarity at the community level.